Formation and inhibition mechanism of novel angiotensin I converting enzyme inhibitory peptides from Chouguiyu - Yang, Daqiao; Li, Laihao; Li, Chunsheng; Chen, Shengjun; Deng, Jianchao; Yang, Shaoling (Frontiers in Nutrition, 2022)
Angiotensin I converting enzyme (ACE) inhibitory peptides from fermented foods exhibit great potential to alleviate hypertension. In this study, the peptide extract from Chouguiyu exhibited a good inhibition effect on ACE and the inhibition rate was significantly enhanced after fermentation for 8 d. The ACE inhibitory peptides were further identified, followed by their inhibition and formation mechanisms using microbiome technology and molecular docking. A total of 356 ACE inhibitory peptides were predicted using in silico, and most ACE inhibitory peptides increased after fermentation. These peptides could be hydrolyzed from 94 kinds of precursor proteins, mainly including muscle-type creatine kinase, nebulin, and troponin I. P1 (VEIINARA), P2 (FAVMVKG), P4 (EITWSDDKK), P7 (DFDDIQK), P8 (IGDDPKF), P9 (INDDPKIL), and P10 (GVDNPGHPFI) were selected as the core ACE inhibitory peptides according to their abundance and docking energy. The salt bridge and conventional hydrogen bond connecting unsaturated oxygen atoms in the peptides contributed most to the ACE inhibition. The cleavage proteases from the microbial genera in Chouguiyu for preparing these 7 core ACE inhibitory peptides were further analyzed by hydrolysis prediction and Pearson’s correlation. The correlation network showed that P7, P8, and P9 were mainly produced by the proteases from LAB including Lactococcus, Enterococcus, Vagococcus, Peptostreptococcus, and Streptococcus, while P1, P2, P4, and P10 were mainly produced by Aeromonas, Bacillus, Escherichia, and Psychrobacter. This study is helpful in isolating the proteases and microbial strains to directionally produce the responding ACE inhibitory peptides.